1994
DOI: 10.1103/physrevlett.73.340
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Heat-Induced Exchange Coupling through Amorphous Silicon

Abstract: We show that ferromagnetic films separated by a spacer of amorphous Si are exchange coupled for Si thicknesses ds;~40 A. For 14 A~ds, & 22 A we observe antiferromagnetic coupling. The coupling strength of approximately 5 X 10 6 J/m-' is strongly temperature dependent with a positive temperature coefficient. We suggest that localized electronic defect states in the gap of amorphous Si mediate the exchange interaction. The particular coupling mechanism encountered here also works with noncrystalline ferromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
57
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 11 publications
1
57
0
Order By: Relevance
“…Multilayer systems consisting of Fe/Si or Fe/FeSi are candidates for new electronic devices, because it is possible to change the size of the magnetic coupling by light [Mattson et al (1993)] or heat [Briner and Landolt (1994); Inomata et al (1995); Highmore et al (1995)]. Therefore, it is necessary to understand which features in ‡uence the associated variables.…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer systems consisting of Fe/Si or Fe/FeSi are candidates for new electronic devices, because it is possible to change the size of the magnetic coupling by light [Mattson et al (1993)] or heat [Briner and Landolt (1994); Inomata et al (1995); Highmore et al (1995)]. Therefore, it is necessary to understand which features in ‡uence the associated variables.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] This coupling sometimes appears to be distinct from the very low temperature tunneling phenomena between two ferromagnets, through a dielectric spacer layer, [6][7][8][9] as the coupling is sometimes oscillatory. [2][3][4][5] There is an increasing body of evidence that impurities, in the insulating layer, will ''dope'' the insulating layer and alter the net polarization of electrons injected into the insulating layer, [10][11][12][13][14][15][16][17] with strong temperature effects, 12,14 most recently demonstrated in Cr 2 O 3 .…”
mentioning
confidence: 99%
“…16,[20][21][22] From the outset, i.e., from the initial stages of surface preparation, the core level binding energies indicated that the stable surfaces were Cr 2 O 3 . The native Cr 2 O 3 surface on CrO 2 22 was used as a native insulating spacer layer between CrO 2 and Co, as has been undertaken elsewhere. 19 Samples were fabricated with 20-, 40-, and 60-Å-thick are nominally antiferromagnetic, with Néel temperatures around 297 and 307 K, respectively, by considering the fact that Néel temperature decreases in very thin films, the samples studied in this work appear to behave much like a ferromagnetic/paramagnetic insulator/ferromagnetic trilayer system in the temperature range of 240-400 K. We used in situ longitudinal MOKE to obtain the hysteresis loops, before and after cobalt deposition, as described elsewhere.…”
mentioning
confidence: 99%
“…The most inter esting experimental investigations of the structural and magnetic properties have been reported for Fe/Si [7⎯11] and Co/Si [10][11][12][13][14][15][16][17][18][19] thin film systems. Analysis of the available data showed that the antiferromagnetic exchange between iron layers in Fe/Si/Fe systems was observed for silicon layer thicknesses within 1.4-1.7 and 1.4-2.2 nm (see, e.g., [20,21]). However, data on the exchange interaction between magnetic layers via nonmagnetic spacers in Co/Si/Co thin film systems are rather contradictory.…”
mentioning
confidence: 99%
“…As for the mechanism of exchange coupling between magnetic layers in the presence of a semiconductor spacer, it differs from the case of a metallic interlayer. According to the existing notions [20,21], a possible mechanism of this exchange in Fe,Co/Si/Fe,Co thin film systems is related to the tunneling of polarized electrons via localized defect states which are always present in the semiconductor layer.…”
mentioning
confidence: 99%